Rekomendasi BUMDes Sebagai Solusi Masalah Pemasaran Hasil Produksi Pertanian Desa Hutabagasan - Yuni Mittra Simanullang; Tuti Atika (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The development of local community of Satahi Tani farming group in Hutabagasan Village aims to explore the problem faced and find solutions to overcome them. The method used in the devotion of the Satahi Tani peasant group is the Delbeq Method which is supported by FGD (Focus Group Discustion) tools aimed at focusing the topic of discussion. The results of the development of "satahi tani" revealed, the problem faced together is the absence of guaranteed prices of agricultural products (marketing). Of the five programs of the "Satahi tani" farming group, three of them suffered losses due to low prices of agricultural production, even though the quantity and quality of production products were good.  Based on the problem, a common solution was produced, namely the recommendation of the formation of a BUMDes. The formation of BUMDes is outlined in a policy paper as an intervention from the results of FGD that has been carried out. The policy paper has been submitted to the Hutabagasan village government as a means of connecting the aspirations of "Satahi Tani". Furthermore, invite the group "Satahi Tani" to restore the production function of the group.